Quantitative assessment of shrub-grass mosaic development in grazed shrublands: An example in the Patagonian Monte (Argentina) - Pazos, Gustavo Enrique (2010)
Grazing alters the spatial structure of shrubs and perennial grasses in desert shrub communities. The resulting spatial distribution of shrub-grass patches constitutes a sensitive indicator of the integrated result of grazing impacts on them. While several procedures were developed to estimate the size of shrub clumps, metrics of the geometry of the interacting grass matrix received less attention. In this study, we conceptualised the spatial structure of shrub-grass patches as consisting of two components: a grass crown of ill-defined outer borders (the 'grass component') encircling a shrub clump (the 'shrub component'). We fitted exponential functions to autocorrelograms of spatially explicit shrub-grass cover data surveyed at different locations of the Patagonian Monte (Argentina) differing in livestock grazing pressure. After that, we derived two metrics from the function parameters that quantitatively estimate the size of both the shrub and the grass components of shrub-grass patches. The patterns of variation of these metrics are consistent with field measurements and observations previously reported for the studied areas, indicating that they are sensitive indicators of the state of development of the shrub-grass mosaic under different grazing pressures. These results suggest that its applicability to similar semi-arid shrublands deserves further attention.